PERLINDUNGAN HUKUM BAGI PEMEGANG HAK GADAI BERDASARKAN HUKUM ADAT TOLAKI DI KECAMATAN WAWOTOBI KABUPATEN KONAWE - Ni Nyoman Triana Suskendariani; Karmila Karmila (Fakultas Hukum Universitas Lakidende, 2022)
Legal certainty of a land pawn agreement carried out using customary law in the Tolaki community is guaranteed by the customary law concerned because the dispute resolution that occurs is also resolved through a customary court, and the existence of the decision of the customary court that binds the disputing parties in addition to the application of strict sanctions in dispute resolution. In addition, the existence and existence of customary law is also supported by the provisions of the applicable legislation, which can be seen in Law Number 4 of 2004 concerning The provisions of the Basic Provisions of Judicial Power, in Article 28 paragraph (1) which states